MENINGKATKAN AKTIVITAS BELAJAR SISWA DENGAN MODEL PEMBELAJARAN GROUP INVESTIGATION PADA MATA PELAJARAN IPS KELAS IV SDN 106184 SEKIP T.A 2020/2021 - Indah Permata Putri; Wiwik Lestari (REKOGNISI : Jurnal Pendidikan dan Kependidikan, 2020)
This study investigates the implementation of the Group Investigation learning model to enhance students' learning activities in Social Studies for fourth-grade students at SDN 106184 Sekip in the academic year 2020/2021. The theoretical framework includes concepts of learning, learning activities, and the Group Investigation learning model. The research method employed is the Group Investigation cooperative learning model, emphasizing student participation in independently seeking and understanding lesson materials. The results and discussion indicate that the implementation of the Group Investigation learning model effectively enhances students' learning activities. Data from the pre-cycle questionnaire shows that only 21% of students were categorized as active, while 79% were categorized as inactive. In Cycle I, the number of active students increased to 44.12%, and in Cycle II, all students were actively involved with a percentage of 100%. The average percentage score of the learning activity questionnaire also increased from 62.97% in Cycle I to 87.23% in Cycle II. This study confirms that the Group Investigation learning model can be an effective strategy to encourage active student participation and improve learning effectiveness in classrooms, particularly in the context of Social Studies at the elementary school level.